WPEDIS – wetting pattern estimator under drip irrigation systems - Al-Ogaidi, Ahmed A. M.; Wayayok, Aimrun; Kamal, Md. Rowshon; Abdullah, Ahmad Fikri (Faculty of Engineering, Universiti Putra Malaysia, 2016)
The dimensions of the wetted soil zone under drip irrigation systems are of considerable practical importance in designing these systems. The selection of proper spacing between emitters and suitable distance between laterals is mainly related to the wetting pattern dimensions. In this study, an empirical model was developed to predict the dimensions of the wetted soil zone under drip irrigation systems. The developed model includes empirical equations to estimate the main dimensions of the wetted soil zone as well as its ability to predict the full shape of the wetting pattern. Series of laboratory experiments were carried out under surface and subsurface emitters using two soil textures, two application rates, and two soil profiles. Application time, emitter discharge, initial moisture content, saturated hydraulic conductivity, bulk density, and the percentages of sand, silt, and clay of the soil are the main inputs of the proposed model. The performance of the model was assessed by comparing the measured and predicted results statistically by considering some statistical criteria such as mean error, root mean square error, and model efficiency. A good agreement between the observed and predicted wetting patterns was achieved which reflects the model suitability in design drip irrigation systems.